Communicative Learning Approach in Improving Students’ Critical Thinking Skills - Hijrah, Hijrah (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
The present research aims to assess the influence of the communicative approach on the cognitive abilities and linguistic competence of students. This study utilized a quasi-experimental approach, specifically adopting a pretest-posttest control group design. The research sample comprised 54 students in the tenth grade. The findings indicated a considerable improvement in the language proficiency of the students in the experimental group. The average score on the posttest increased by 18.7 points, from 60.2 to 78.9. The experimental group exhibited a substantial enhancement in their critical thinking abilities, with scores increasing from 51.38 to 83,04 in contrast to a lesser improvement shown in the control group. The data suggest that the communicative method is successful in strengthening students' language proficiency, as well as improving their critical thinking capabilities. Based on this study, it is recommended that the communicative approach be more extensively incorporated into the learning process. This would entail reinforcing teacher education, increasing infrastructure, and modifying the curriculum accordingly. The findings have significant use in formulating learning techniques in vocational schools, specifically in equipping students to confront workforce issues.